2016
DOI: 10.1589/jpts.28.3310
|View full text |Cite
|
Sign up to set email alerts
|

The effects of visual biofeedback using ultrasonograpy on deep trunk muscle activation

Abstract: [Purpose] The objective of this study is to investigate the effect of visual biofeedback using ulatrasonography on the functional improvement of deep trunk muscle. [Subjects and Methods] This study selected ten healthy people without orthopedic history and information on the study. The average ages, heights, and weights were 22.70 ± 2.06 years old, 171.15 ± 9.18 cm, and 66.86 ± 8.88 kg in the experimental group, respectively. The abdominal drawing-in maneuver were executed for subjects through monitoring the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…(Salik Sengul et al, 2021) Trunk training employing unstable surfaces, for example, therapy ball, increases trunk muscle activity and may remedy side‐to‐side asymmetries (Van Criekinge et al, 2019); side‐to‐side asymmetries have been previously reported post‐LLA. (Sions et al, 2021) Visual biofeedback using ultrasound imaging may enhance lumbar multifidi activity (Cha et al, 2016) and be more effective than tactile and/or verbal cueing alone, particularly for retaining gains in muscle activity between treatment sessions. (Van Criekinge et al, 2019) Of note, however, multifidi activity elicited with single limb lifts, while safe in terms of imparted spinal loading, may not produce sufficient muscle activity to evoke desired extensor muscle strength gains (i.e., >50% of a maximal volitional contraction).…”
Section: Discussionmentioning
confidence: 99%
“…(Salik Sengul et al, 2021) Trunk training employing unstable surfaces, for example, therapy ball, increases trunk muscle activity and may remedy side‐to‐side asymmetries (Van Criekinge et al, 2019); side‐to‐side asymmetries have been previously reported post‐LLA. (Sions et al, 2021) Visual biofeedback using ultrasound imaging may enhance lumbar multifidi activity (Cha et al, 2016) and be more effective than tactile and/or verbal cueing alone, particularly for retaining gains in muscle activity between treatment sessions. (Van Criekinge et al, 2019) Of note, however, multifidi activity elicited with single limb lifts, while safe in terms of imparted spinal loading, may not produce sufficient muscle activity to evoke desired extensor muscle strength gains (i.e., >50% of a maximal volitional contraction).…”
Section: Discussionmentioning
confidence: 99%